2022
DOI: 10.1038/s41598-022-07301-5
|View full text |Cite
|
Sign up to set email alerts
|

Viral load of SARS-CoV-2 in droplets and bioaerosols directly captured during breathing, speaking and coughing

Abstract: Determining the viral load and infectivity of SARS-CoV-2 in macroscopic respiratory droplets, bioaerosols, and other bodily fluids and secretions is important for identifying transmission modes, assessing risks and informing public health guidelines. Here we show that viral load of SARS-CoV-2 Ribonucleic Acid (RNA) in participants’ naso-pharyngeal (NP) swabs positively correlated with RNA viral load they emitted in both droplets >10 $$\upmu \hbox {m}$$ μ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 61 publications
2
32
0
Order By: Relevance
“…For virus inactivation experiments we added 10 5 PFUs of SARS-CoV-2 diluted in 0.5 ml of infection medium (MEM with 0.2% bovine serum albumin, 2mM glutamine and 20mM Hepes) to sterile polystyrene 100 mm culture dishes (Corning, Corning, NY). The virus concentration used for drying (2 × 10 5 PFU/ml) was approximately 10-fold higher than that present in droplets from highly-infectious individuals, for whom a maximum of 1.8 × 10 4 PFU/ml of SARS-CoV-2 was detected in nasopharingeal swabs [16] . We spreaded the virus inoculum on each plate using a spatula and let it dry inside a biosafety hood for 30 min.…”
Section: Methodsmentioning
confidence: 95%
“…For virus inactivation experiments we added 10 5 PFUs of SARS-CoV-2 diluted in 0.5 ml of infection medium (MEM with 0.2% bovine serum albumin, 2mM glutamine and 20mM Hepes) to sterile polystyrene 100 mm culture dishes (Corning, Corning, NY). The virus concentration used for drying (2 × 10 5 PFU/ml) was approximately 10-fold higher than that present in droplets from highly-infectious individuals, for whom a maximum of 1.8 × 10 4 PFU/ml of SARS-CoV-2 was detected in nasopharingeal swabs [16] . We spreaded the virus inoculum on each plate using a spatula and let it dry inside a biosafety hood for 30 min.…”
Section: Methodsmentioning
confidence: 95%
“…Studies found that the viral load in patients' nasopharyngeal swabs is positively correlated with viral loads emitted in both droplets and aerosols, and with environmental contamination. 21 , 22 , 23 Multivariate analyses have identified that viral load (viral RNA) larger than 10 7 copies/ml (OR = 14.7) is independently associated with isolation of infectious virus from respiratory tract samples. 13 Numerous studies have demonstrated that higher SARS‐CoV‐2 viral load in the upper airway of an infected person is associated their increased infectivity.…”
Section: Shedding and Dissemination Of Sars‐cov‐2 From Infected Indiv...mentioning
confidence: 99%
“…The first step in developing a model of respiratory particle emission is to physically characterize the particles. Respiratory particles are heterogeneous and vary in number, size, chemical composition, and viral content depending on the generation mechanism, the stage of infection, as well as inter- and intra-subject variability [ 32 , 36 , 69 , 70 ]. Accounting for this heterogeneity is an important step in quantifying the potential uncertainty in particle emission from an infected individual.…”
Section: Appendix A1 Particle Generationmentioning
confidence: 99%
“…For the indoor environment, a value of 0 m/s can be assumed for wind speed, resulting in an inhalable fraction of ~0 for 100-micron particles. To determine likelihood of infection from an exposure environment, the model first accounts for how many particles are inhaled, the location of deposition, and the particle composition; this is determined by considering particle-size dependent inhalability [ 57 ], particle size-dependent deposition site [ 78 ] (which would also account for hygroscopic growth of a particle as it enters the humid respiratory tract [ 20 ]), and the viral content of particles [ 70 ]. The severity and course of illness of the disease then could depend solely on demographic factors, immune response, deposited dose, or a combination of factors.…”
Section: Appendix A1 Particle Generationmentioning
confidence: 99%
See 1 more Smart Citation